(untitled) (Far Eastern Federal University: School of Engineering Bulletin, 2025)
The problem of utilization of such industrial waste as fly ash (FA) and ground blast furnace granulated slag (GBGS) is currently relevant and requires solutions aimed at its elimination. The purpose of this study is to develop environmentally friendly and cost-effective concrete compositions manufactured using industrial waste. A total of 13 experimental concrete compositions were manufactured with a portion of cement replaced with FA and GBGS from 0 to 30% with a step of 5%. The properties of concrete mixtures and concretes were studied. Based on the results of experimental studies, it was found that the optimal amount of replacement of a portion of cement for both FA and GBGS is 15%. The increase in compressive strength for concrete with FA was 18.6%, for concrete with GBGS – 14.4%. Water absorption values ​​decreased by 15.2 and 13.7%, respectively. The results obtained during the study prove that the proposal to use industrial waste in the form of fly ash and ground blast furnace granulated slag in the production of concrete is rational and allows solving the problem of their disposal. The concretes themselves have improved properties and are more environmentally friendly and economical.